Cissus quadrangularis in Bone Healing and Oxidative Stress - Nathirat Charoensup; Kittisak Sangthong; Watis Kongcharoen (Journal of Advances in Medicine and Pharmaceutical Sciences, 2024)
Cissus quadrangularis is a plant known for its traditional use in bone healing, has shown potential in modern pharmacological applications due to its bioactive compounds. This study investigates the therapeutic effects of Cissus quadrangularis extract on bone healing, antioxidant activity, and gastric protection. The primary objective was to evaluate its efficacy in accelerating bone regeneration, mitigating oxidative stress, and protecting the gastric mucosa from NSAID-induced damage. The methodology involved a series of in vivo experiments using rats, with treatment groups receiving the extract and control groups given a placebo. Bone healing was assessed radiographically, antioxidant activity was measured using the DPPH assay and SOD enzyme activity, and gastric protection was evaluated by counting gastric lesions. The findings revealed a 40% improvement in bone healing, a 25% increase in SOD activity, and a 60% reduction in gastric lesions in the treatment group compared to controls. These results suggest that Cissus quadrangularis has significant potential as a natural remedy for bone fractures, oxidative stress, and gastric ulcers. Future research should focus on human clinical trials, molecular mechanisms, and long-term safety to support its broader medical application.